COVID-19: Erroneous Modelling and Its Policy Implications - Yinon Bar-On; Tatiana Baron; Ofer Cornfeld; Ron Milo; Eran Yashiv (Institute of Labor Economics (IZA), 2021)
Research in Economics on COVID-19 posits an economy subject to disease dynamics, which are often seriously misspecified in terms of speed and scale. Using a social planner problem, we show that such misspecifications lead to misguided policy. Erroneously characterizing a relatively slow-moving disease engenders dramatically higher death tolls and excessive output loss relative to the correct benchmark. We delineate the latter, employing epidemiological evidence on the timescales of COVID-19 transmission and clinical progression. The resulting sound model is simple, transparent, and novel in Economics.
Keywords: E61; E65; H12; J17; 330; optimal policy; public health; GDP loss; COVID-19; disease dynamics and scale; misspecification